Impact of a Bundle of Interventions on Quality-of-Care Indicators for Staphylococcus aureus Bacteraemia: A Single-Centre, Quasi-Experimental, Before-After Study - Giacomo Casalini; Cristina Pagani; Andrea Giacomelli; Laura Galimberti; Laura Milazzo; Massimo Coen; Serena Reato; Beatrice Caloni; Stefania Caronni; Simone Pagano; Samuel Lazzarin; Anna Lisa Ridolfo; et al. (MDPI AG, 2024)
Staphylococcus aureus bacteraemia (SAB) is a life-threatening bloodstream infection. Improved adherence to quality-of-care indicators (QCIs) can significantly enhance patient outcomes. This quasi-experimental study evaluated the impact of a bundle of interventions on QCI adherence in adult patients with SAB. Additionally, a molecular rapid diagnostic test (mRDT) for S. aureus and methicillin resistance was introduced during weekdays. We compared pre-intervention (January-December 2022) and post-intervention (May 2023-April 2024) data on QCI adherence and time to appropriate treatment. A total of 56 and 40 SAB episodes were included in the pre- and post-intervention periods, respectively. Full QCI adherence significantly increased from 28.6% to 67.5% in the post-intervention period (p < 0.001). The mRDT diagnosed SAB in eight cases (26.6%), but the time to achieve appropriate target therapy did not improve in the post-intervention period (54 h (IQR 30-74) vs. 72 h (IQR 51-83), p = 0.131). The thirty-day mortality rate was comparable between the two periods (17.9% vs. 12.5%, p = 0.476). This study demonstrates that a bundle of interventions can substantially improve adherence to SAB management QCIs.